Minat Mahasiswa Universitas Warmadewa Menjadi Wirausaha - Dewa Putu Widjana; I Made Artawan (Universitas Warmadewa, 2019)
Abstract - The role of the university in developing interest in entrepreneurship and exploring some of the factors that influence entrepreneurial behavior have been explored by several researchers. These studies explain that entrepreneurial interest that can be directed through entrepreneurship education is influenced by attitudes and interests in entrepreneurship. This research is analyze students interest in entrepreneurship with a sample of Universitas Warmadewa students. The methods of this research is through questions in the questionnaire. Warmadewa University has 10,516 active students. Therefore, the aims of this research is to find out the interest of Warmadewa University students to do entrepreneurship. The researcher distributed 485 questionnaires to Warmadewa University Students, which were feasible to use for analysis. Data analysis techniques used in this study used frequency distribution. Frequency distribution is the arrangement of data according to certain classes. At the data presentation stage, data that has been classified, presented or displayed in table form. The results of the study showed that as many as 31% of students from Warmadewa University had made an entrepreneur or had a business. As many as 51% of businesses that have been occupied are mostly still active. As many as 37% of students from Warmadewa University became entrepreneurs. As many as 16.7% of students from Warmadewa University wanted to pay if entrepreneurial class activities were held on campus. As many as 41.3% of students from Warmadewa University had the fighting spirit to become entrepreneurs. the activity of marketing a product, is still weak as much as expressing doubt. Abstrak - Peran universitas dalam mengembangkan minat berwirausaha dan menggali beberapa faktor yang berpengaruh pada perilaku berwirausaha telah digali oleh beberapa peneliti. Penelitian-penelitian tersebut menjelaskan bahwa minat kewirausahaan yang dapat diarahkan melalui pendidikan kewirausahaan dipengaruhi oleh sikap dan minat terhadap kewirausahaan. Penelitian ini meneliti minat mahasiswa terhadap kewirausahaan pada mahasiswa Universitas Warmadewa. Metode yang digunakan dalam penelitian ini dikaji melalui pertanyan dalam kuesioner. Universitas Warmadewa memiliki jumlah mahasiswa aktif sebanyak 10.516 orang. Oleh karena itu, tujuan dari penelitian ini adalah untuk mengetahui minat mahasiswa Universitas Warmadewa untuk melakukan wirausaha.Penelitian ini menggunakan metode sensus, dengan populasi adalah mahasiswa Universitas Warmadewa. Peneliti menyebarkan kuesioner kepada Mahasiswa Universitas Warmadewa sebanyak 485, yang layak digunakan untuk analisis. Teknik analisis data yang digunakan dalam penelitian ini menggunakan distribusi frekuensi. Distribusi frekuensi adalah susunan data menurut kelas-kelas tertentu. Pada tahap penyajian data, data yang sudah diklasifikasikan, disajikan atau ditampilkan dalam bentuk tabel. Hasil Penelitian menunjukkan Sebanyak 31% Mahasiswa Universitas Warmadewa telah melakukan wirausaha atau telah mempunyai usaha. Sebanyak 51% usaha yang telah ditekuni kebanyakan masih aktif. Sebanyak 37% keinginan Mahasiswa Universitas Warmadewa untuk menjadi wirausaha.Sebanyak 16,7% Mahasiswa Universitas Warmadewa mau membayar jika dilaksanakan kegiatan kelas kewirausahaan di kampus.Sebanyak 41,3% Mahasiswa Universitas Warmadewa mempunyai jiwa/daya juang untuk menjadi seorang wirausaha harus tahan banting dalam kegiatan memasarkan suatu produk, ternyatak masih lemah sebesar menyatakan ragu-ragu.